Chronic Kidney Disease-Associated Pruritus - Puneet Agarwal; Vinita Garg; Priyanka Karagaiah; Jacek C. Szepietowski; Stephan Grabbe; Mohamad Goldust (Toxins, 2021)
Pruritus is a distressing condition associated with end-stage renal disease (ESRD), advanced chronic kidney disease (CKD), as well as maintenance dialysis and adversely affects the quality of life (QOL) of these patients. It has been reported to range from 20% to as high as 90%. The mechanism of CKD-associated pruritus (CKD-aP) has not been clearly identified, and many theories have been proposed to explain it. Many risk factors have been found to be associated with CKD-aP. The pruritus in CKD presents with diverse clinical features, and there are no set features to diagnose it.The patients with CKD-aP are mainly treated by nephrologists, primary care doctors, and dermatologists. Many treatments have been tried but nothing has been effective. The search of literature included peer-reviewed articles, including clinical trials and scientific reviews. Literature was identified through March 2021, and references of respective articles and only articles published in the English language were included.